Correlation between HbA1c Levels with Carotid Intima Media Thickness in Newly Diagnosed Type 2 Diabetes Mellitus Patients - Reza Pramayudha; Chaerul Achmad; Erwinanto Erwinanto; Januar W. Martha; M.Rizki Akbar (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
Background: Type 2 diabetes mellitus (T2DM) is the most common chronic disease in the world. Macrovascular complications such as cardiovascular and cerebrovascular diseases can be detected early, one of them by using an ultrasound examination to assess carotid intima-media thickness (CIMT). HbA1c examination had a strong predictive value for the occurrence of T2DM complications. HbA1c levels are associated with CIMT in the non-DM group. In the T2DM group there was an increase in CIMT compared to the non DM group. HbA1c levels can be used as a predictor of the progression of CIMT improvement in the T2DM group, but there is no study on populations with newly diagnosed T2DM.Aims: This study was conducted to find out the correlation between HbA1c in newly diagnosed T2DM and CIMT.Methods: This was a cross-sectional study with correlation analysis carried out on newly diagnosed T2DM in four Primary Health Centers in the city of Bandung who were randomly selected from July to August 2018. HbA1c measurement was carried out at Dr. Hasan Sadikin hospital. The CIMT examination was done according to the Manheim Consensus by a cardiologist. Pearson correlation analysis was performed to assess the relationship between those two variables.Results: This study involved 32 subjects with a median age of 52 (40 - 60) years. The mean value of CIMT was 0.77±0.22 mm, while the median value of HbA1c was 6.7 (5.2- 12.3). Bivariate analysis showed a moderate positive correlation between HbA1c and CIMT in newly diagnosed patients with T2DM. (r= 0.567, p<0.001).Conclusion: There was a significant positive correlation between HbA1c in newly diagnosed T2DM and CIMT.